Effect of Job Satisfaction on Employee Performance (Study of PT Antarmitra Sembada, West Jakarta Logistics Division) - Zackharia Rialmi; Iis Noviyanti; Ryan Akbar (Kusuma Negara Business School, 2020)
This study aims to determine the extent of job satisfaction (Variable X) and performance (Variable Y) at PT Antarmitra Sembada Division of Logistics West Jakarta and to determine the extent of job satisfaction (Variable X) on employee performance (Variable Y) at PT Antarmitra Sembada Division. West Jakarta Logistics. The author's hypothesis test design uses the assumption that Ho is accepted if t <ttable and Ho is rejected if tcount> ttable. The method used by the author is associative, while quantitative data is used to analyze the data. Data management used data validity test, data reliability test, Pearson correlation coefficient analysis, simple linear regression test, determination coefficient analysis and hypothesis testing. The population in writing this thesis is the employees of PT Antarmitra Sembada, West Jakarta Logistics Division, as many as 60 people, and the sample in this paper is a questionnaire. Based on the results of the simple linear regression test, it states that job satisfaction (X), employee performance (Y) will still be formed at 21.7207 and job satisfaction at 0.4482. The correlation coefficient test value of 0.456 has a moderate effect. While the value of the determination coefficient is 20.8%, the data identifies that job satisfaction contributes to the influence of employee performance by 20.8%, the remaining 79.2% is influenced by other factors that the author is not careful about and the value of the results of the hypothesis test, the value of tcount is 4.383> t table 2.00 then Ho is rejected and Ha is accepted. From these results indicate that job satisfaction has a significant effect on employee performance at PT Antarmitra Sembada, West Jakarta Logistics Division.